Identification of the genetic mechanism that associates L3MBTL3 to multiple sclerosis. Issue 13 (28th January 2022) - Alcina, Antonio; Fedetz, Maria; Vidal-Cobo, Isabel; Andrés-León, Eduardo; García-Sánchez, Maria-Isabel; Barroso-del-Jesus, Alicia; Eichau, Sara; Gil-Varea, Elia; Luisa-Maria Villar,; Saiz, Albert; Leyva, Laura; Vandenbroeck, Koen; et al.
Abstract: Multiple sclerosis (MS) is a complex and demyelinating disease of the central nervous system. One of the challenges of the post-genome-wide association studies (GWAS) era is to understand the molecular basis of statistical associations to reveal gene networks and potential therapeutic targets. The L3MBTL3 locus has been associated with MS risk by GWAS. To identify the causal variant of the locus, we performed fine mapping in a cohort of 3440 MS patients and 1688 healthy controls. The variant that best explained the association was rs6569648 ( P  = 4.13E-10, odds ratio = 0.71, 95% confidence interval (CI) = 0.64–0.79), which tagged rs7740107, located in intron 7 of L3MBTL3. The rs7740107 (A/T) variant has been reported to be the best expression and splice quantitative trait locus (eQTL and sQTL) of the region in up to 35 human genotype-tissue expression (GTEx) tissues. By sequencing RNA from blood of 17 MS patients and quantification by digital qPCR, we determined that this eQTL/sQTL originated from the expression of a novel short transcript starting in intron 7 near rs7740107. The short transcript was translated into three proteins starting at different translation initiation codons. These N-terminal truncated proteins lacked the region where L3MBTL3 interacts with the transcriptional regulator Recombination Signal Binding Protein for Immunoglobulin Kappa J Region which, in turn, regulates the Notch signalling pathway. Our data and other functional studies suggest that the genetic mechanism underlying the MS association of rs7740107 affects not only the expression of L3MBTL3 isoforms, but might also involve the Notch signalling pathway.